Public Sector Reforms in India: New Role of the District Officer - Chandan Sinha (Sage, 2007)
This book brings into perspective the processes and impact of public sector reforms that have gone virtually unnoticed by studying developments that have quietly, but irreversibly, altered the way the indian state provides goods and services to its citizen-costumers